Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Berbantuan Wordwall terhadap Motivasi Belajar IPAS Kelas V di SDN 46 Cakranegara - Luthfiyah Maulida; Siti Rohana Hariana Intiana; Fitri Puji Astria (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study focuses on improving the low motivation of fifth-grade students in science learning at SDN 46 Cakranegara through the use of innovative learning models and media. This problem is caused by learning activities that only rely on textbooks and note-taking without utilizing more interesting learning media with the material presented. This study aims to determine the effect of the cooperative learning model of the teams games tournament (TGT) type assisted by wordwall media on the motivation of fifth-grade students in science learning at SDN 46 Cakranegara. This type of research is quantitative research with a Quasi-Experimental design of the Nonequivalent Control Group Design type. The sampling technique uses saturated sampling. The population consists of 20 people in the experimental class and 20 in the control class. The data analysis technique uses the t-test, but previously a prerequisite test in the form of a normality test was carried out, obtained normally distributed data with a significance value of > 0.05. The results of the Pretest  and Posttest  homogeneity tests obtained sig. of 0.531 and 0.714 which means > 0.05 then the data is declared homogeneous. The results of the hypothesis test were obtained through the independent sample t-test getting sig. (2-tailed) 0.004 < 0.05 and the calculated t value ≥ t table is 3.036 ≥ 2.024, which means Ha is accepted and Ho is rejected. Furthermore, the N-Gain test obtained a gain of 0.4919 which indicates a moderate level of influence. Based on the results of the study, it can be concluded that there is an influence of the use of the teams games tournament learning model assisted by wordwall media on the motivation to learn science in class V at SDN 46 Cakranegara with a large influence of 0.4919 which is included in the moderate category.